2009
DOI: 10.1086/592945
|View full text |Cite
|
Sign up to set email alerts
|

Blackjack in the Kitchen: Understanding Online versus Casino Gambling

Abstract: About $10 billion a year is spent by consumers worldwide on online gambling, and that number continues to grow. We present a qualitative, image-based study of 30 Las Vegas online and casino gamblers. By examining online gambling as a consumption experience, we examine what happens to consumption meaning as gambling moves away from a regulated physical space to an unregulated online space, one accessed from home. We explore the meaning of online gambling consumption to consumers and flesh out the social welfare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(82 citation statements)
references
References 36 publications
(36 reference statements)
1
80
0
1
Order By: Relevance
“…While it is tempting to conclude the Internet may enable problematic gambling behaviour, it is more likely that problem gamblers are more frequent gamblers in general and gamble on a wider range of activities, including activities via the Internet. The reasons individuals offer for gambling online tend also to be factors that have the potential to lead to sustained and problematic gambling (i.e., ease of access, flexibility of use, 24-hour availability, large gambling choice, and anonymity) (Cotte & Latour, 2009;Griffiths & Barnes, 2008). Because there are relatively few barriers to access, the Internet may well be providing a facilitating factor in the excessive gambling of vulnerable individuals, in particular young people and problem gamblers (Griffiths & Barnes, 2008).…”
Section: Problem Gambling and The Internetmentioning
confidence: 99%
“…While it is tempting to conclude the Internet may enable problematic gambling behaviour, it is more likely that problem gamblers are more frequent gamblers in general and gamble on a wider range of activities, including activities via the Internet. The reasons individuals offer for gambling online tend also to be factors that have the potential to lead to sustained and problematic gambling (i.e., ease of access, flexibility of use, 24-hour availability, large gambling choice, and anonymity) (Cotte & Latour, 2009;Griffiths & Barnes, 2008). Because there are relatively few barriers to access, the Internet may well be providing a facilitating factor in the excessive gambling of vulnerable individuals, in particular young people and problem gamblers (Griffiths & Barnes, 2008).…”
Section: Problem Gambling and The Internetmentioning
confidence: 99%
“…conflict, relapse, and mood modification), as well as greater overall scores of addiction than online players. A study by Cotte and Latour (2009) has revealed several differences between online and the traditional (casino) gamblers. The two main differences were the perceptions of social connectedness and anonymity.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, online players, apart from the comfort of joining the game from home, may also avoid social interaction by playing on the Internet. Plainly said, many online players would not go to a casino or poker playroom, whereas many traditional players would not play online (Cotte & Latour, 2009). The feelings and emotions in traditional gambling are also more vivid and more intense than in online games.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, online gambling has become more socially accepted in contemporary societies and it has been integrated into many individual's everyday lives (Cotte and Latour, 2009;Kuss and Griffiths, 2012). However, technological advances and the growth of remote gambling (via the internet, mobile phones, and interactive television) can be negatively detrimental to some individuals (Wardle, Moody, Griffiths et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As the integration of gambling into everyday lives has shown individuals losing track of their spending (Auer and Griffiths, 2016;Siemens and Kopp, 2011), the concern about individual and social harm has grown (Canale, Veino & Griffiths, 2016;Yani-de-Soriano et al, 2012). In this sense, online gambling has been considered to be more harmful and less regulated than traditional gambling (Cotte and Latour, 2009;Kuss and Griffiths, 2012).…”
Section: Introductionmentioning
confidence: 99%